A characterization of finite arithmetic progressions via regular partitions of quadrilaterals. Issue 3 (2nd April 2020) - Vincenzi, Giovanni
ABSTRACT: In this article, we will give a geometric interpretation of certain finite arithmetic progressions. For this purpose, we will introduce the concept of the n - regular partition P n of a quadrilateral.